Two Rare Mollusk Records for Wisconsin - Harold A. Mathiak (Hello World!, 1974)
On September 13, 1973 I found two specimens of Elliptio complanatus (Dillwyn) in the South fork of the flambeau River in Price County. Baker (1928, The Fresh water Mollusca of Wisconsin, Part II) considered this a very rare species in Wisconsin, it having been found in only two places in the west end of Lake Superior at his time.